2020
DOI: 10.3389/fonc.2020.591577
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Non-Genetic Mechanisms of Resistance to BCR Signaling Inhibitors in B Cell Malignancies

Abstract: The approval of BTK and PI3K inhibitors (ibrutinib, idelalisib) represents a revolution in the therapy of B cell malignancies such as chronic lymphocytic leukemia (CLL), mantle-cell lymphoma (MCL), diffuse large B cell lymphoma (DLBCL), follicular lymphoma (FL), or Waldenström’s macroglobulinemia (WM). However, these “BCR inhibitors” function by interfering with B cell pathophysiology in a more complex way than anticipated, and resistance develops through multiple mechanisms. In ibrutinib treated patients, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 211 publications
(244 reference statements)
0
42
0
4
Order By: Relevance
“…However, the response to ibrutinib is variable and several different mechanisms of ibrutinib resistance have been described ( 23 ). It is important to understand the mechanism and pathways involved in resistance or sensitivity to BCR pathway inhibitors in order to most effectively treat B-cell malignancies ( 24 ).…”
mentioning
confidence: 99%
“…However, the response to ibrutinib is variable and several different mechanisms of ibrutinib resistance have been described ( 23 ). It is important to understand the mechanism and pathways involved in resistance or sensitivity to BCR pathway inhibitors in order to most effectively treat B-cell malignancies ( 24 ).…”
mentioning
confidence: 99%
“…However, the responses to ibrutinib in MCL patients appears not be lasting and relapse usually happens. Other than mutation in BTK gene itself, relative resistance to ibrutinib can be caused by non-genetic adaptive mechanisms leading to compensatory pro-survival pathway activation such as NF-κB ( 53 ). Our present study showed that GPER agonist G-1 inactivates NF-κB pathway and appears to have a synergistic effect with ibrutinib on inhibiting proliferation in MCL cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying role of included genetic alterations for development and progression of CLL is still largely unknown. There is also growing evidence which implicates aberrant signaling through the mTOR pathway in B cell malignancies [ 182 , 215 , 216 ].…”
Section: Methodsmentioning
confidence: 99%